New Zealand petrel translocation diets : an assessment of three Procellariiformes diets : grey faced petrel (Pterodroma macroptera gouldi; kuia), Chatham petrel (Pterodroma axillaris; ranguru) and fluttering shearwater (Puffinus gavia; pakahā) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Science in Wildlife Health at Massey University, Manawatū, New Zealand - Jensen, Micah Anna (Massey University, 2021)
In New Zealand, a pureed diet of Brunswick tinned sardines™ in soya oil (S/Soy) has been widely fed to Procellariiformes chicks during translocations. The diet provides high fledging rates, however, when fed for longer periods diseases have occurred that may be related to malnutrition and may impact fledgling survival at sea. The effect of dietary oils was compared in feeding trials by substituting soya oil with fish oil during chick translocations of two burrow nesting petrel species. Fish oil supplemented diets were fed to 30 of 76 grey-faced petrel chicks (Pterodroma macroptera gouldi; kuia) (GFP) combined with a Mazuri fish analogue® (M/Fish), and to 20 of 74 fluttering shearwater chicks (Puffinus gavia; pakahā) (FS) fed a puree of Brunswick tinned sardines™ in spring water (S/Fish). Changes in red blood cell (RBC) phospholipid fatty acid composition, fledging parameters, and necropsy results were compared over the 3-week translocation period as well as return rates thereafter. Fledging parameters were similar between the diet groups, with GFP chicks that were fed the S/Soy diet fledging at significantly higher weights. Deaths due to visceral gout occurred in GFP chicks irrespective of the diet fed. Feeding fish oil improved fledging RBC phospholipid fatty acid ratios to levels that resemble wild seabird diets, with significantly higher docosahexaenoic acid C22:6n3 (DHA) and arachidonic acid C20:4n6 (ARAC); fatty acids that are important for cellular communication as eicosanoids and are vital for immune responses in birds. In contrast, chicks fed soya oil had significantly higher proportions of linoleic acid C18:2n6 (LIN) resulting in RBC membranes that were filled with plant-based 18-carbon fatty acids, which may not be metabolizable in some obligate piscivorous seabirds. DHA levels were significantly decreased which could have a deleterious effect on chick maturation. Until the exact nutritional requirements of seabirds are known a prudent diet would include fish oils that are already present in wild marine-based diets. Return rates of FS nine years later have not shown any difference in effect from the oil-fed. The three species of petrel were investigated to represent three, distinctly different foraging strategies: GFP as long-distance foragers, FS as short-distance daily feeders and Chatham petrel (Pterodroma axillaris; ranguru) (CP) as an endangered species that are long-distance foragers, yet have a restricted range during the chick-rearing season. The nutrient composition and fatty acid components of proventricular samples for each species were analysed and compared to three different translocation dietary groups (S/Soy, M/Fish and S/Fish). The effect of sampling methods on nutrient analysis was compared between proventricular flushing (PVF) and spontaneous regurgitation (REG). Results showed that GFP diets were highly variable in nutritional composition and the sampling method had a significant effect on results, with REG samples demonstrating higher fat content. Ash content was highly variable in all species, particularly samples collected by PVF, and increased the variation reported in proximate analysis results. Yet, irrespective of the sampling method used, the differences between all species were widely apparent. Species with a short-foraging strategy (FS) show higher protein and lower fat content compared with those with long-foraging strategies (GFP and CP). The fatty acid proportions of PVF samples were not greatly affected by sampling methods but showed diversity when compared between species and translocation dietary groups. The artificial diet S/Soy had significantly higher proportions of LIN and alpha-linolenic acid C18:3n3 (ALIN) than any other group, setting it apart distinctly from all other wild diets as well as artificial diets supplemented with fish oil. DHA and ARAC were lower in the soya oil diet than in both the fish oil supplemented diets and in the GFP wild diet. Oleic acid C18:1n9 (OLE) and palmitic acid C16:0 (PAL) were the predominant fatty acids in wild diets and showed species-specific differences. No artificial diet provided sufficient nervonic acid C24:1n9 (NERV) to reach levels in wild diets, with tinned sardines in fish oil being the closest alternative. The CP wild diet was uniquely high in NERV and its n-9 precursors (OLE, eicosenoic acid C20:1n9 and erucic acid C22:1n9), with markedly low DHA, docosapentaenoic acid C22:5n3 (DPA), eicosapentaenoic acid C20:5n3 (EPA), and ARAC levels in comparison to other species, wild diets, and translocation dietary groups. Translocation diets based on tinned sardines with supplemented fish oil showed closest similarity to the wild diets of all species studied. Given the dietary importance of long-chain polyunsaturated fatty acids (PUFAs) for the health and development of chicks, a prudent diet would include supplementation with DHA, ARAC and NERV fortified oils. The volume and proportion of fat-fed in the diet needs further investigation, with careful consideration of the sampling methods used to determine normal fat levels within the diet.
Keywords: 300999 Veterinary sciences not elsewhere classified